2014
DOI: 10.1016/j.nut.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-rich Rutgers Scarlet Lettuce improves glucose metabolism and liver lipid accumulation in diet-induced obese C57BL/6 mice

Abstract: Objective The aims of the following experiments were to characterize anti-diabetic in vitro and in vivo activity of the polyphenol-rich aqueous extract of Rutgers Scarlet Lettuce. Materials / Methods Rutgers Scarlet Lettuce (RSL) extract (RSLE) and isolated compounds were evaluated for inhibitory effects on glucose production as well as tumor necrosis factor alpha (TNFα)-dependent inhibition of insulin activity in H4IIE rat hepatoma cells. Additionally, high fat diet-induced obese mice were treated with RSLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Furthermore, the hepatocytes size in CPO group was smaller than HPO and EAO groups and those in EAO group was bigger than HPO group. Previous studies have shown that squalene, tocopherols, and polyphenols could improve hepatic steatosis and correct atherosclerosis (Chang, Peng, Yeh, Kao, & Wang, ; Cheng et al., ; Daugherty, Tall, Mjap, Falk, & Fishe, ; Eun‐Young et al., ; Lavine et al., ). These indicated that bioactive compounds in CPO, HPO, and EAO may answer for these results.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hepatocytes size in CPO group was smaller than HPO and EAO groups and those in EAO group was bigger than HPO group. Previous studies have shown that squalene, tocopherols, and polyphenols could improve hepatic steatosis and correct atherosclerosis (Chang, Peng, Yeh, Kao, & Wang, ; Cheng et al., ; Daugherty, Tall, Mjap, Falk, & Fishe, ; Eun‐Young et al., ; Lavine et al., ). These indicated that bioactive compounds in CPO, HPO, and EAO may answer for these results.…”
Section: Resultsmentioning
confidence: 99%
“…RSL looseleaf variety NFR, was provided by Shamrock Seed Co. (Salinas, CA) and green leaf lettuce (GL) variety Crispa (Andy Boy, Salinas, CA) were purchased from the grocery store (Stop and Shop, Highland Park, NJ). NFR plant and seed vouchers were made and deposited at the Chrysler Herbarium and ATCC . Outer leaves and tops of RSL lettuce heads were used as they have the highest levels of phenolics.…”
Section: Methodsmentioning
confidence: 99%
“…Trunk blood was into tubes containing EDTA (BD, Franklin Lakes, NJ) centrifuged for 10 min at 1000 × g (within the first 30 min) and plasma was collected and stored at ≤ −20°C. Plasma was sent to Pennington Biomedical Research Center (PBRC, Baton Rouge, LA) for biochemical analysis of glucose, insulin, triglycerides, free fatty acids, and lipopolysaccharide (LPS) concentrations, as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on prevention and treatment of obesity and its associated health risks using plant-derived phenolic compounds. The nutritional effects of phenolic compounds have been well established in their role in modulating specific physiological functions in rodents and human beings (5,6). Ferulic acid (FA) (Figure 1) belongs to the family of phenolic acids and is very abundant in fruits, vegetables and grains, such as rice bran, oats, wheat, barley, roasted coffee, tomatoes, asparagus, berries, vegetables, citrus fruits and leaves of most plants.…”
Section: Introductionmentioning
confidence: 99%